Meeting National Service Framework goals for patients presenting with acute myocardial infarction. Issue 2 (1st March 2003) - Gilby, E; Lloyd, G; Chan, L; Tosh, S; Brierley, S
Abstract : Background: The National Service Framework for coronary heart disease established clear standards for the management of patients with acute myocardial infarction in March 2000. This study evaluates an emergency department's thrombolysis performance in light of these standards. Setting: Inner city teaching hospital emergency department. Methods: The data were prospectively collected using a formal clinical pathway for all patients receiving thrombolysis in the emergency department between February 2000 and January 2001. Cases were reviewed at monthly multidisciplinary audit meetings. Regular feedback complemented routine teaching for both nursing and medical staff. Results: 127 patients were thrombolysed, of whom 92 (72%) were immediately eligible. Some 77% of these had a door to needle time of less than 30 minutes and 38% less than 20 minutes. Twenty per cent of patients had a call to door time of less than 30 minutes. Some 84% of patients managed by the emergency department team had a door to needle time of less than 30 minutes compared with 53% of those patients seen by duty physicians. Conclusions: The thrombolysis target set by the National Service Framework for April 2002 is achievable. The target set for April 2003 remains an ambitious goal. Overall call to needle times are undermined by call to door times. Emergency department teams may be more efficient than duty physicians in processing patients needing thrombolysis.